A small-mammal survey at Tasek Bera, Pahang, Malaysias first ramsar site - - S.Syakirah, - A. Zubaid, - C. Prentice, - A. Lopez, - M.R. Azmin, - A. Mohd Yusof, (N/A, 2000)
A small-mammal survey at Tasek Bera, Pahang, Malaysias first ramsar site by - S.Syakirah, - A. Zubaid, - C. Prentice, - A. Lopez, - M.R. Azmin, - A. Mohd Yusof,